Vocabulary Learning in Chinese as a Second Language: Exploring the Role of Self-Regulation in Facilitating Vocabulary Knowledge of Second Language Learners - Zhu, Sida; Wang, Cong (Frontiers in Psychology, 2022)
Vocabulary knowledge comprises depth and breadth, which are regarded as important indicators of L2 learning capability. Self-regulation is a key factor in promoting vocabulary knowledge. However, the role and contribution of depth and breadth to L2 learning, as well as the predictive role of different factors of self-regulation to depth and breadth, remain unclear. Therefore, this study aims to identify the relationship between vocabulary knowledge and self-regulation by establishing a structural equation model based on exploratory factor analysis and confirmatory factor analysis using self-regulation and vocabulary knowledge (depth and breadth) questionnaires. A total of 215 Vietnamese university students participated in the research. The results show that Vietnamese university students generally obtain high scores in breadth, but their scores vary in depth, which indicate although most of them can accurately understand some aspects of Chinese word meaning, they are not able to command the form and usage of words. In addition, there is a negative correlation between self-regulation and vocabulary breadth, which demonstrates that high self-regulation, especially emotional control, can affect Vietnamese university students’ vocabulary learning. This study also proposes some suggestions for Chinese vocabulary teaching.